Pediatric suppurative parotitis caused by Burkholderia pseudomallei. Issue 1 (December 2016) - Fu, Zengzhen; Lin, Yingzi; Wu, Qiang; Xia, Qianfeng
Abstract Background Suppurative parotitis caused byBurkholderia pseudomallei has been rarely found outside endemic areas. Case presentation Herein, we report the recovery ofBurkholderia pseudomallei from the pus of a suppurative parotitis observed in a 12-year-old boy who lived in Hainan province, China. Specimens of necrotic tissue were collected and sections were stained with hematoxylin and eosin. Pus sample was also collected for bacteriological examination. The suppurative inflammation was observed in the necrotic tissue section andBurkholderia pseudomallei were detected in the sample. Conclusion In this adolescent, Burkholderia pseudomallei infection was present in the parotid, which consists of the first report of this bacterium in a parotitis case acquired in China.